Effect of Additional Cu on Structural and Optical Properties of TiO2 Synthesized with Sol-Gel Method - Sidauruk, Anggi Natasya; Amal, Muhamad Ikhlasul; Marlianto, Eddy (Journal of Technomaterial Physics, 2022)
In this study, TiO2 doped with Cu has been successfully synthesized using the sol-gel method by varying the addition of Cu and the calcination temperature. Sample preparation was started by mixing 0.75 mL of 37% HCl in 49.25 mL of 96% ethanol and stirred with a magnetic stirrer for 10 minutes. Then 10 mL of TTIP (Titanium Tetraisopropoxide) was added dropwise using a dropper and the solution was stirred again with a magnetic stirrer for 60 minutes. Then added Cu with variations of 1%, 2%, 3%, 4%, and 5% and stirred again for 60 minutes using a magnetic stirrer. The sol solution was then put into the furnace at a temperature of 100°C for 3 days. The crystalline sol solution was then mashed with a mortar to a submicron size, then washed with 50 mL of Aquades and stirred using a magnetic stirrer for 10 minutes. The washed samples were then dried in a furnace at a temperature of 100°C for 1 day. Followed by calcination for 3 hours with temperature variations of 450°C, 500°C, 550°C and 600°C to release the gases in the nanoparticles. Cu-doped TiO2 nanoparticles were characterized using test equipment such as XRD, SEM-EDX, and UV-Vis. From the results of XRD analysis obtained 3 phases namely Brookite, Rutile and Anastase, and the crystal size is unstable and the shape of the sample particles is tetragonal. The results of the SEM-EDX analysis showed that the content of the sample was in accordance with the experiments that had been carried out. The results of UV-Vis analysis show that the wavelength is inversely proportional to the bandgap energy.